They live [videorecording (Blu-Ray)] - Foster, Meg; Piper, Roddy, 1954-2015; David, Keith; Armitage, Frank; Franco, Larry J.; Carpenter, John, 1948- (Shout Factory, 2012)
When two men put on special sunglasses they see aliens and subliminal messages.